Pesantren Strategies in Maintaining Islamic Education Traditions and Shaping Santri Social Identity in the Midst of Social Change - Mubarak Mubarak; Nuryadin Nuryadin; Galuh Nashrulloh Kartika MR; Isna Radiyah; Mukmin Mukmin (Pascasarjana Universitas KH. Abdul Chalim, 2026)
Pesantren is a traditional Islamic educational institution currently facing significant pressure from globalization and modernization, which disrupt conventional values. This study aims to analyze the strategies employed by pesantren in preserving Islamic educational traditions while examining the process of shaping students' (santri) social identity amidst dynamic social changes. This research utilized a descriptive qualitative approach within Creswell’s framework. Data were collected through in-depth interviews with leaders (Kyai) and teachers, participatory observation within the pesantren environment, and documentation of curriculum transitions. The results reveal that pesantren implement a hybrid strategy by maintaining kitab kuning (classical texts) learning and the sorogan and bandongan systems as the primary spiritual foundation. Adaptation to social change is achieved through the integration of the national curriculum, digital skills training, and strengthening santri entrepreneurship. The Kyai plays a central role as a charismatic authority figure who balances authentic traditional values with the necessity of modern innovation. The social identity of santri is formed through the internalization of sincerity, simplicity, and independence, practiced collectively in daily life. The study concludes that pesantren demonstrate high resilience in maintaining their Islamic identity despite structural adjustments. The implications of this research highlight the importance of value-based education models as a reference for developing other Islamic educational institutions in facing global challenges without losing their cultural and spiritual roots.